Optimization of Stellorice Ice Cream Made from Soy Milk and Jack Bean Flour as a Nutritious Snack for School-Age Children - Astri Vidila Sari; Rina Martini (Media Publikasi Cendekia Indonesia, 2026)
School-aged children (6–12 years old) need adequate nutrition to support their growth and development. The habit of consuming unhealthy snacks in the school environment can lead to nutritional problems in children. Therefore, there is a need for snack alternatives that children enjoy and that have good nutritional value. This study aims to develop a soy milk ice cream product with the addition of jack bean flour. Additionally, butterfly pea flower extract is used as a natural coloring agent to make the ice cream’s color more appealing. An experimental method was employed, with three formulations incorporating jack bean flour at levels of 5%, 10%, and 15%. A hedonic test was conducted with 54 untrained panelists, specifically sixth-grade elementary school students. Data analysis for physical properties—specifically overrun and melting point—was performed using ANOVA and Duncan’s test, while hedonic evaluations of color, aroma, taste, and texture were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The resulting ice cream was named Stellorice and for the three formulations showed that the addition of jack bean flour had a significant effect on overrun and melting point, as well as on hedonic evaluations related to texture parameters; however, there was no significant effect on color, aroma, and taste. The selected formulation was F2, with the addition of 50 grams of jack bean flour. This ice cream product has an energy content of 133 kcal, 4.2 grams of protein, 4 grams of fat, and 19.7 grams of carbohydrates, as well as an overrun of 44.8% and a melting time of 57 minutes.